Comparative analysis on arthroscopic sutures of large and extensive rotator cuff injuries in relation to the degree of osteopenia - Alexandre Almeida; Vinícius Atti; Daniel Cecconi Agostini; Márcio Rangel Valin; Nayvaldo Couto de Almeida; Ana Paula Agostini (Revista Brasileira de Ortopedia, 2015)
OBJECTIVE: To analyze the results from arthroscopic suturing of large and extensive rotator cuff injuries, according to the patient's degree of osteopenia.METHOD: 138 patients who underwent arthroscopic suturing of large and extensive rotator cuff injuries between 2003 and 2011 were analyzed. Those operated from October 2008 onwards formed a prospective cohort, while the remainder formed a retrospective cohort. Also from October 2008 onwards, bone densitometry evaluation was requested at the time of the surgical treatment. For the patients operated before this date, densitometry examinations performed up to two years before or after the surgical treatment were investigated. The patients were divided into three groups. Those with osteoporosis formed group 1 (n = 16); those with osteopenia, group 2 (n = 33); and normal individuals, group 3 (n = 55).RESULTS: In analyzing the University of California at Los Angeles (UCLA) scores of group 3 and comparing them with group 2, no statistically significant difference was seen (p = 0.070). Analysis on group 3 in comparison with group 1 showed a statistically significant difference (p = 0.027).CONCLUSION: The results from arthroscopic suturing of large and extensive rotator cuff injuries seem to be influenced by the patient's bone mineral density, as assessed using bone densitometry.